A legal study on the constitutional rights of transgender in Malaysia: with special reference to the legal position in India / Ellifamira Azisman, Najwa Hanee Md Hazza and Nur Sabihah Shukri - Azisman, Ellifamira; Md Hazza, Najwa Hanee; Shukri, Nur Sabihah (2014)
It is observed that the current laws in Malaysia do not recognize the gender of transgender and this does not guarantee them of their constitutional rights such as their legal status, civil liberties and their fair chance of employment and living which leaves them to be in a legal limbo. This study is to provide recommendations that may improve the legislative framework relating to the improvement with regards to the welfare of the transgender community in Malaysia which could be done through facilitating a fairer and more effective method in performing legal recognitions of the transgender people's status. It has to be acknowledged that first there is a new term introduced by the American Psychiatric Association (APA), which is "gender dysphoria", substituting the previous terminology of gender identity disorder. Furthermore, this study will be focused on the status quo of the legal status of the transgender in Malaysia and the effect of reformation of the law as to their legal recognition and the change of their gender and name in both their Identity Card (MyKad) and birth certificate. Besides that, a comparative study is also done between the implementation of the law regarding the transgender with another country which is India with its current approach, following the Supreme Court's decision in the case of National Legal Service Authority v Union of India & Ors, where they had introduced a third gender category.